Pendampingan Kelompok Usaha Kemplang Panggang dalam Upaya Peningkatan Produktivitas Masyarakat Desa Tebing Utara Kabupaten Ogan Ilir - Lili Erina; Rizka Azzahri; Aji Pangestu; Angga Christopel Immanuel Lumban Tobing; M. Alvido Mashanriza (Pusat Riset dan Inovasi Nasional, 2025)
Mentoring for a roasted kemplang (shrimp cake) business group in Tebing Utara Village focused on increasing production capacity, quality, and product consistency through simple yet effective appropriate technology. The program was implemented in five stages: outreach, training, technology implementation, mentoring and evaluation, and program sustainability. Interventions included the use of dough rolling machines, gas stoves, and freezers to maintain raw material freshness and expedite the production process. Results showed a 150% increase in production capacity, ±90% consistency of kemplang size, and increased partner ability to operate modern equipment independently. Evaluation of product quality through thickness, texture, and simple taste tests demonstrated significant improvements. This approach not only increased production capacity but also strengthened partner independence, encouraged local innovation, and potentially replicated in other traditional food MSMEs. This mentoring program has had a positive impact on local economic development, increased the competitiveness of roasted kemplang products, and provided relevant training for business owners. Furthermore, the use of appropriate technology has shown effective results in increasing productivity without compromising product quality.